Analisis Penggunaan LKPD Berbasis Sikap Peduli Lingkungan Dalam Pembelajaran IPA di SMP - Yanti Rusdianti; Hendro Prasetyono (Institute of Advanced Knowledge and Science, 2026)
The purpose of this study is to present the results of an analysis of the implementation of environment-based worksheets for students (LKPD) in science education at the elementary school level, with the aim of encouraging student participation in the learning process as well as their ability to collaborate, think critically, and be creative. The research approach used is descriptive with a qualitative design. The data collected includes qualitative data from feedback provided by teachers and students as users of the teaching materials, observations of the learning process, as well as documentation covering the teaching materials used and photographs of learning activities. The research results indicate that the worksheets were systematically designed using the Canva application to produce visually appealing and environmentally relevant content, while emphasizing student engagement and connections to daily life. In the creation of the worksheets, the integration of sustainability principles, optimal readability, and high accessibility were top priorities. Feedback from teachers indicated a high level of satisfaction with the worksheets’ effectiveness in supporting the learning process, while feedback from students highlighted their enthusiasm and deep understanding of environmental topics.